Évaluation Des Pratiques Phytosanitaires Paysannes Dans Les Vergers De Cacao Dans Le Departement De Daloa, Côte d’Ivoire - Martin, Siapo Yao; Annick, Tahiri; Joachim, Ano Ehui; Séraphin, Diby Yao Kan (European Scientific Journal, ESJ, 2018)
This paper focuses on identifying pesticides uses in the protection of cocoa tree. To do this, a survey was conducted among 129 randomly selected cocoa producers in the Daloa zone in Côte d’Ivoire. The results showed that 79.84% of the producers interviewed, use pesticides. Twenty-seven (27) pesticides were identified; among them, 24 were insecticides, 3 were fungicides, and two were not licensed. More than 50% of the insecticides used by famers were neonicotinoids combined with pyrethroids. None of the pesticides was termiticide although termite damage was cited as major. Fiftythree point four percent (53.4%) of producers store pesticides in their house. Empty packs and containers are abandoned in nature after being used by 96% of surveyed farmers, while 4% reused them. The results indicated that producers should be well sensitized on good agricultural practice.